2020
DOI: 10.1007/s00216-020-02878-0
|View full text |Cite
|
Sign up to set email alerts
|

Studying in vitro metabolism of the first and second generation of antisense oligonucleotides with the use of ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry

Abstract: The aim of the present investigation was the analysis and identification of antisense oligonucleotide metabolism products after incubation with human liver microsomes regarding four different oligonucleotide modifications. Separation and detection methods based on the use of liquid chromatography coupled with quadrupole time-of-flight mass spectrometry were developed for this purpose. Firstly, the optimization of mass spectrometer parameters was done to select those which ensure the highest possible sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Despite the well-known fact that phosphorothioate and 2′- O -methoxyethyl modifications decrease nuclease-mediated degradation, nusinersen was metabolized [ 15 , 18 , 19 , 29 , 30 ]. The 3′end shortmers and 5′end shortmers were generated and identified in serum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the well-known fact that phosphorothioate and 2′- O -methoxyethyl modifications decrease nuclease-mediated degradation, nusinersen was metabolized [ 15 , 18 , 19 , 29 , 30 ]. The 3′end shortmers and 5′end shortmers were generated and identified in serum.…”
Section: Resultsmentioning
confidence: 99%
“…All of these parameters were changed for similar chromatographic conditions: 5–80 % v / v MeOH in 15 min for 5 mM DMBA/150 mM HFIP; flow rate 0.3 mL/min; 1 μL injection; autosampler temperature 30 °C, column temperature 50 °C, column Kinetex 1.7 µm EVO C18 (100 × 2.1 mm) (Phenomenex, Torrance, CA, US). The other Q-TOF-MS parameters, such as drying gas flow (10 L/min), shielding gas flow (10 L/min), octopole voltage (800 V), drying gas temperature (350 °C), and shielding gas temperature (400 °C) were selected based on our previous experience with antisense OGNs studies using Q-TOF-MS [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…These PS-modified ASOs can induce an RNase H-related cleavage of mRNA. The second generation represents oligonucleotides in which the structural modification is not limited to the backbone linkage but includes structural modifications of the ribose: ASO with 2′-O-alkyl modifications of the ribose were developed [ 11 ]. These modifications improve binding affinity, increase efficacy, decrease the protein binding of oligonucleotides, and enhance nuclease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our research in this paper is focused on developing new efficient strategies for antibacterial drug discovery that may lead to a shorter development time and a higher success rate of drug candidate discovery. Our approach combines synthetic biology methods, bioinformatics [ 4 , 5 ], and rational drug design of antisense oligonucleotides (ASOs) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Herein, we employ ASO that binds explicitly with the complementary sequence of the S-adenosyl methionine (SAM-I) riboswitch located in the 5′-untranslated region (UTR) of mRNAs and inhibits the growth of pathogenic human bacteria, such as S. aureus and Listeria (L.) monocytogenes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Husser and co-workers have shown that LC-MS can be sensitive enough to determine the cleavage points and metabolites of oligonucleotides conjugated with GalNAc, a ligand that can grant greater potency through high affinity liver targeting but also causes changes in the biotransformation of oligonucleotides [9,10]. More recent publications by Kim and co-authors have described the development of an LC-MS method for the 2 -O-methyl modified phosphorothioate ASO eluforsen and its metabolites [8], and Kilanowska and co-authors have described the in vitro metabolism of various modified and different length ASOs with human liver microsomes using LC-MS [11]. Nevertheless, there remain challenges in using LC-MS for quantitation.…”
mentioning
confidence: 99%